A Novel Luminescence-Based High-Throughput Approach for Cellular Resolution of Protein Ubiquitination Using Tandem Ubiquitin Binding Entities (TUBEs). (April 2020) - Akinjiyan, Favour A.; Fazal, Aleem; Hild, Marc; Beckwith, Rohan E. J.; Ross, Nathan T.; Paulk, Joshiawa; Carbonneau, Seth
Protein turnover is highly regulated by the posttranslational process of ubiquitination. Deregulation of the ubiquitin proteasome system (UPS) has been implicated in cancer and neurodegenerative diseases, and modulating this system has proven to be a viable approach for therapeutic intervention. The development of novel technologies that enable high-throughput studies of substrate protein ubiquitination is key for UPS drug discovery. Conventional approaches for studying ubiquitination either have high protein requirements or rely on exogenous or modified ubiquitin moieties, thus limiting their utility. In order to circumvent these issues, we developed a high-throughput live-cell assay that combines the NanoBiT luminescence-based technology with tandem ubiquitin binding entities (TUBEs) to resolve substrate ubiquitination. To demonstrate the effectiveness and utility of this assay, we studied compound-induced ubiquitination of the G to S Phase Transition 1 (GSPT1) protein. Using this assay, we characterized compounds with varying levels of GSPT1 ubiquitination activity. This method provides a live-cell-based approach for assaying substrate ubiquitination that can be adapted to study the kinetics of ubiquitin transfer onto a substrate protein of interest. In addition, our results show that this approach is portable for studying the ubiquitination of target proteins with diverse functions.